Forensic psychology for dummies - Canter, David (Chichester, England : Wiley a John Wiley and Sons, Ltd., Publication, 2012)
A fascinating guide on the psychology of crime Thinking of a career that indulges your CSI fantasies? Want to understand the psychology of crime? Whether studying it for the first time or an interested spectator, Forensic Psychology For Dummies gives you all the essentials for understanding this exciting field, complemented with fascinating case examples from around the world. Inside you'll find out why people commit crime, how psychology helps in the investigative process, the ways psychologists work with criminals behind bars - and how you too can become a forensic psychologist. You'll discover what a typical day is like for a forensic psychologist, how they work with the police to build offender profiles, interview suspects or witnesses, and detect lies! Law, order, and the criminal mind-- a fascinating introduction to forensic psychology and its many applications.
Introduction -- Nailing forensic psychology: a moving target -- Helping the police solve crimes -- Measuring the criminal mind -- Viewing psychology in court -- Helping and treating offenders -- The part of tens.
Includes index.
Keywords: FORENSIC PSYCHOLOGY